Bacterial type II toxin-antitoxin systems acting through post-translational modifications - Si-Ping Zhang (Computational and Structural Biotechnology Journal, 2021)
The post-translational modification (PTM) serves as an important molecular switch mechanism to modulate diverse biological functions in response to specific cues. Though more commonly found in eukaryotic cells, many PTMs have been identified and characterized in bacteria over the past decade, highlighting the importance of PTMs in regulating bacterial physiology. Several bacterial PTM enzymes have been characterized to function as the toxin component of type II TA systems, which consist of a toxin that inhibits cell growth and an antitoxin that protects the cell from poisoning by the toxin. While TA systems can be classified into seven types based on nature of the antitoxin and its activity, type II TA systems are perhaps the most studied among the different TA types and widely distributed in eubacteria and archaea. The type II toxins possessing PTM activities typically modify various cellular targets mostly associated with protein translation and DNA replication. This review mainly focuses on the enzymatic activities, target specificities, antitoxin neutralizing mechanisms of the different families of PTM toxins. We also proposed that TA systems can be conceptually viewed as molecular switches where the ‘on’ and ‘off’ state of the system is tightly controlled by antitoxins and discussed the perspective on toxins having other physiologically roles apart from growth inhibition by acting on the nonessential cellular targets.